LQR-BASED ACTIVE SEAT SUSPENSION DESIGN TO IMPROVE BUS DRIVER RIDE COMFORT - Sekulic, Dragan (Journal of Applied Engineering Science, 2026)
Bus drivers are exposed to vibrations generated by the road surface affecting their fatigue, comfort and health. Vibrations are transmitted from bus wheels to the driver’s body through bus suspension system, bus floor and the seat suspension system. Active and semi-active seat suspensions have been developed to alleviate vibrational negative effects. This paper investigated bus driver ride comfort as a function of bus speeds and road quality considering linear quadratic regulator for active seat suspension system. A 3-degree-of-freedom intercity bus model had been defined for simulation. Bus modelling, controller design and simulations were performed by MATLAB/Simulink software. Results showed that active seat suspension significantly reduces the vertical acceleration transmitted to the driver’s body compared to the passive system. Improvements were particularly noticeable on rough roads and at higher bus speeds.
Keywords: passive and active seat suspension, LQR design, bus, ride comfort, simulation